(untitled) (World Bulletin of Management and Law, 2024)
Currently, in the arsenal of doctors there is a large selection of drugs with regenerative and reparative properties. However, none of them are universal and their effectiveness is far from optimal. This necessitates the search and development of new drugs for the treatment of burn injuries.